The Effect of Work Situation and Unsafety Action on Work Accident in PT. Raja Marga Nagan Raya District - Sriwahyuni, Susy; Santika, Eka; Khairunnas, Khairunnas; Ishalyadi, Ishalyadi; Fahlevi, Muhammad Iqbal (Universitas Teuku Umar, 2020)
A work accident is an unplanned event that has the potential to cause injury, damage or other loss to someone. Based on preliminary studies conducted by researchers to 10 employees that the work environment is less than the maximum one of which is caused by a workplace environment that is too hot, muddy, slippery and easily causes employees to slip. The aims of research to determine the factor of affecting work accident. The research used analytic survey with cross sectional approach. The population were all employees (72 respondents) and used total sampling and used chi-square test. The results showed there were effect among work situation (Pvalue = 0.011) and unsafety action (Pvalue = 0,000) with work accident. The researcher suggest to PT. Raja Marga to provide warning letters to employees in an effort to avoid work accidents to the maximum extent.